Characteristics of Agricultural Extension Workers in Bangka Selatan Regency - Yulia Yulia; Eddy Jajang Jaya Atmaja; Monica Kharisma Swandi (Journal of Global Sustainable Agriculture, 2024)
Extension workers are agents of change in development who are required to be knowledgeable and keep up with information developments in today's era, so that the material in their extension activities always contains useful information for farmers. The current digital era provides ease of access, sharing, and utilization of information through digital information technology and rapid communication. This research aims to describe the characteristics and behaviors of agricultural extension workers in the digital era in Bangka Selatan Regency, Bangka Belitung Islands Province. The method used in this study is qualitative descriptive. The results from the field indicate that out of 35 respondents, the individual characteristics in this study are dominated by male extension workers, with the highest percentage of educational background being Bachelor's degree. The age distribution of extension workers in this study shows that the majority are young, between 36 to 47 years old. The number of non-civil servant (NON ASN) extension workers is greater than that of civil servant (ASN) extension workers in this study. This is due to a program from the local agricultural office regarding the procurement of extension workers with NON ASN status or as assistant agricultural extension workers. The number of NON ASN extension workers dominates the total number of ASN extension workers. To enhance their skills and competencies, extension workers typically receive non-formal education in the form of training, seminars, and workshops, averaging 3-5 times a year. Regarding their work experience, some extension workers have been in the field for a long time, around 11-20 years, while others have been working for a shorter period, ranging from 1-10 years.